Molecular details on multiple cofactor containing redox metalloproteins revealed by infrared and resonance raman spectroscopies - Silveira, Célia M. (2022)
Funding Information: Funding: This research was funded by FEDER funds through COMPETE2020—Programa Opera-cional Competitividade e Internacionalização (POCI) and by national funds through FCT—Fundacão para a Ciência e a Tecnologia, grant Project LISBOA-01-0145-FEDER-007660 (Microbiologia Molecular, Estrutural e Celular). S.T. acknowledges grant PTDC/BTM-SAL/29507/2017, C.M.S. acknowledges grant PTDC/BIA-BFS/31026/2017 project, and C.B. acknowledges fellowship 2020.05017.BD all funded by FCT. G.C., I.Z., and P.H. are grateful for funding from the Einstein Foundation Berlin (grant number EVF-2016-277). This work was also supported through the cluster of excellence “UniSysCat“ funded by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) under Germany’s Excellence Strategy-EXC2008/1-390540038 and the SPP 1927 ”Iron Sulfur for Life”—ZE 510/2-2 (IZ). The APC was funded by the TIMB3 project, European Union’s Horizon 2020 research and innovation program, under grant agreement No 810856. Funding Information: This research was funded by FEDER funds through COMPETE2020?Programa Opera-cional Competitividade e Internacionaliza??o (POCI) and by national funds through FCT?Fundac?o para a Ci?ncia e a Tecnologia, grant Project LISBOA-01-0145-FEDER-007660 (Microbiologia Molecular, Estrutural e Celular). S.T. acknowledges grant PTDC/BTM-SAL/29507/2017, C.M.S. acknowledges grant PTDC/BIA-BFS/31026/2017 project, and C.B. acknowledges fellowship 2020.05017.BD all funded by FCT. G.C., I.Z., and P.H. are grateful for funding from the Einstein Foundation Berlin (grant number EVF-2016-277). This work was also supported through the cluster of excellence ?UniSysCat? funded by the Deutsche Forschungsgemeinschaft (DFG, German Research Founda-tion) under Germany?s Excellence Strategy-EXC2008/1-390540038 and the SPP 1927 ?Iron Sulfur for Life??ZE 510/2-2 (IZ). The APC was funded by the TIMB3 project, European Union?s Horizon 2020 research and innovation program, under grant agreement No 810856. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.